Shrinkage of concrete using porous aggregates - Valgeir Ó. Flosason 1987- (2014)
During its service life, concrete undergoes volume changes which can affect quality and durability of the concrete. There are several types of volume changes, but shrinkage is the type of volume change which is often responsible for cracking of the concrete. Shrinkage can be categorized due to several different mechanisms which cause shrinkage. The main types of shrinkage are plastic shrinkage, chemical shrinkage, autogenous shrinkage, drying shrinkage and carbonation shrinkage. In this master thesis a research on variable factors regarding shrinkage of concrete was conducted. The main focus was to examine the effects of aggregates on concrete shrinkage, effects of specimen size on shrinkage measurements, the use of shrinkage compensating concrete as a solution in order to reduce shrinkage and the magnitude of long-term shrinkage. For this examination, 34 different lab-concrete mixes were produced at Innovation Center Iceland and measured for shrinkage. Also, several results based on former research were used to assess long-term effects of shrinkage. The results on the effects of aggregates revealed that the grading seems to have insignificant effects on shrinkage. The overall difference between Vatnsskarð aggregates and Björgun aggregates is small compared to the difference between the Norwegian aggregates and the Icelandic aggregates. Moisture content in aggregates seems to affect shrinkage, as the concrete containing oven-dry aggregates developed both less shrinkage and weight loss compared to concrete containing saturated surface-moist aggregates. Specimen size influenced both the rate of shrinkage and the magnitude. Shrinkage seems to be higher at early stages when the volume/surface ratio is lower, but later on in the hydration process, shrinkage increases as the volume/surface ratio increases. Effect of curing on shrinkage was found to be a complex phenomenon. It is difficult to establish the benefits of curing on total shrinkage based on the results, as some samples developed higher shrinkage when ...